استخدام وسيلة البطاقة المصورة لترقية قدرة الطلبة على مهارة الكلام في المدارس المتوسطة الإسلامية - Humaira, Siti; Ridha, Muhammad; Abdullah, Abdullah; Ninoersy, Tarmizi (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2024)
Based on the first observation at MTsN 2 Aceh Besar the researcher found that student are difficulty in learning Arabic lessons, especially in speaking skills, they cannot use words in speaking, and also they are afraid of making mistakes when speaking arabic. Because the teacher only uses one learning method, is discovery learning, and the teacher does not used the right media in learning process.To overcome this problem, researcher want yo use of picture card media to improve speaking skills students.The purpose of this study was to determine the effectiveness of using picture card media to improve speaking skills students and to find out the activities of teacher and students during the learning process of using picture card media. In this study, researcher used experimental research with the design of One Group Pre-Test Post-Test Design. For data collection, researcher use pre-test and post-test, and researcher also use direct observation. The result of this study incate that the result of pre-test and post-test are with a significiance level (Asymp.Sig. 2-tailed) 0,000 < 0,05. This proves that use of the picture card media is effective to improve speaking skills students. And as for the result of observations of teacher and student activities use of the picture card media, the result obtained very good scores which result reached 87,5%.